The Shark Alar Hypothalamus: Molecular Characterization of Prosomeric Subdivisions and Evolutionary Trends - Santos-Durán, Gabriel N.; Ferreiro-Galve, Susana; Menuet, Arnaud; Quintana-Urzainqui, Idoia; Mazan, Sylvie; Rodríguez-Moldes, Isabel; Candal, Eva (Frontiers in Neuroanatomy, 2016)
The hypothalamus is an important physiologic center of the vertebrate brain involved in the elaboration of individual and species survival responses. To better understand the ancestral organization of the alar hypothalamus we revisit previous data on ScOtp, ScDlx2/5, ScTbr1, ScNkx2.1 expression and Pax6 immunoreactivity jointly with new data on ScNeurog2, ScLhx9, ScLhx5, and ScNkx2.8 expression, in addition to immunoreactivity to serotonin (5-HT) and doublecourtin (DCX) in the catshark Scyliorhinus canicula, a key species for this purpose since cartilaginous fishes are basal representatives of gnathostomes (jawed vertebrates). Our study revealed a complex genoarchitecture for the chondrichthyan alar hypothalamus. We identified terminal (rostral) and peduncular (caudal) subdivisions in the prosomeric paraventricular and subparaventricular areas (TPa/PPa and TSPa/PSPa, respectively) evidenced by the expression pattern of developmental genes like ScLhx5 (TPa) and immunoreactivity against Pax6 (PSPa) and 5-HT (PPa and PSPa). Dorso-ventral subdivisions were only evidenced in the SPa (SPaD, SPaV; respectively) by means of Pax6 and ScNkx2.8 (respectively). Interestingly, ScNkx2.8 expression overlap over the alar-basal boundary, as Nkx2.2 does in other vertebrates. Our results reveal evidences for the existence of different groups of tangentially migrated cells expressing ScOtp, Pax6 and ScDlx2. The genoarchitectonic comparative analysis suggests alternative interpretations of the rostral-most alar plate in prosomeric terms and reveals a conserved molecular background for the vertebrate alar hypothalamus likely acquired before/during the agnathan-gnathostome transition, on which Otp, Pax6, Lhx5, and Neurog2 are expressed in the Pa while Dlx and Nkx2.2/Nkx2.8 are expressed in the SPa.